2014
DOI: 10.3892/ijmm.2014.2002
|View full text |Cite
|
Sign up to set email alerts
|

Taurine induces the apoptosis of breast cancer cells by regulating apoptosis-related proteins of mitochondria

Abstract: Abstract. Taurine (Tau), the most abundant free amino acid in humans has numerous potential health benefits through its antioxidant and anti-inflammatory properties. However, limited studies have assessed its effect on tumors and the antitumor mechanism remains unknown. The present study investigated the cellular and molecular changes induced by Tau, leading to the induction of apoptosis in human breast cancer cell lines MCF-7 and MDA-MB-231. MCF-7 is p53 proficient (p53 +/+ ) and MDA-MB-231 is a p53 null muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 39 publications
1
37
0
2
Order By: Relevance
“…Recent studies have shown that Tau is involved in the most important pathway related to tumor metabolism [20,21]. The anti-tumor mechanism of Tau is mainly related to Tau-induced apoptosis, synergism, and attenuation [913], via regulating the expression of key genes at both the transcriptional and translational levels. For example, Zhang et al showed that Tau prompted the transcription and translation of the PUMA gene in HT-29 colorectal cancer cells [10], and Sorensen et al indicated that Tau increases LRRC8A expression in wild-type A2780 cells [22]; however, the specific mechanisms underlying these effects have not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that Tau is involved in the most important pathway related to tumor metabolism [20,21]. The anti-tumor mechanism of Tau is mainly related to Tau-induced apoptosis, synergism, and attenuation [913], via regulating the expression of key genes at both the transcriptional and translational levels. For example, Zhang et al showed that Tau prompted the transcription and translation of the PUMA gene in HT-29 colorectal cancer cells [10], and Sorensen et al indicated that Tau increases LRRC8A expression in wild-type A2780 cells [22]; however, the specific mechanisms underlying these effects have not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Tau can inhibit the in vitro invasion and migration of breast cancer cells and has a better therapeutic effect against methylbenzanthracene (DMBA)-induced breast cancer [11,12]. Our previous studies have shown that Tau can inhibit the apoptosis of cardiomyocytes subjected to ischemia/reperfusion [15] and can induce (or promote) apoptosis in colon cancer [10], breast cancer [13,14], or liver cancer cells [12]. This effect is achieved by up-regulating the expression of BCL-2, PMA, and P53, while down-regulating the expression of BCL-2.…”
Section: Introductionmentioning
confidence: 99%
“…ER- and HER2+ tumors are generally more aggressive, and when comparing patients with a poor or good prognosis based on clinical parameters (lymphatic spread, tumor size and hormone receptor status) lower taurine levels in tissue from the poor-prognosis patients were detected [39]. A study using two different human breast cancer cell lines showed that treating cells with taurine inhibited growth and induced apoptosis by regulating apoptosis-related proteins of mitochondria [73]. …”
Section: Amino Acid Metabolismmentioning
confidence: 99%
“…Taurine has been found to maintain the level of cysteine, an essential precursor of glutathione and also acts as an antioxidant . Studies have revealed the anticancer and apoptosis‐inducing role of taurine in cancer cells . Inclusion of a small amount of taurine to drinking water has been shown to extend the mean lifespan of mice with transplanted tumors, with a tumor growth inhibition rate of 42.26% .…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion of a small amount of taurine to drinking water has been shown to extend the mean lifespan of mice with transplanted tumors, with a tumor growth inhibition rate of 42.26% . It has been reported that taurine Schiff base copper complex effectively inhibited the activity of purified 20S and 26S proteasomes in human breast cancer MDA‐MB‐231 and leukemia Jurkat T‐cells, which results in the accumulation of ubiquitinated protein and the proteasome target proteins p27 and Bax, followed by the induction of apoptosis …”
Section: Introductionmentioning
confidence: 99%